Determination of Online Customer Reviews and Celebrity Endorsers on Buying Decisions Through Customer Satisfaction - Fadli Adnin Nasution; Aswin Pratama Harahap; Satria Mirsya Affandy Nasution (CERED Indonesia Institute, 2026)
This study aims to analyze the influence of online customer reviews and celebrity endorsers on purchasing decisions for Skintific skincare with customer satisfaction as an intervening variable in Medan City. This type of research is associative with a sample of 96 respondents in Medan City who use Skintific skincare. The data collection technique uses a questionnaire and the data analysis technique uses Partial Least Square (SmartPLS). The results of the study show that there is a positive and significant influence of online customer reviews on buying decisions, there is no influence of celebrity endorsers on purchasing decisions, there is a positive and significant influence of customer satisfaction on buying decisions, there is a positive and significant influence of online customer reviews on customer satisfaction, there is a positive and significant influence of celebrity endorsers on customer satisfaction, there is a positive and significant influence of online customer reviews indirectly on buying decisions through customer satisfaction, and there is a positive and significant influence of celebrity endorsers indirectly on buying decisions through customer satisfaction of Skintific skincare products